Chemical composition in water masses and interactions with the sediment in the southern Weddel sea - Anderson, Leif G; Fogelqvist, Elisabet; Hulth, Stefan; Olsson, Kristina; Tanhua, Toste; Tengberg, Anders; Zemlyak, Frank (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; analyser; kjemisk; sedimenter; vannmasser

Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Characteristics of Weddell Sea Shelf sediments obtained by diamond core drilling, Antarctica - Strand, Kari; Kristoffersen, Yngve (FINNARP -95/96: Weddel Sea Joint Nordic Expedition, 1997)
Keywords: Sørishavet; geokjemi; sedimenter

Glaciomarine sediments and suspended particulate matter, Weddell sea, Antarctica (abstract only) - Elverhøi, Anders; Roaldset, Elen (Annals of Glaciology, 1981)
Samples of glaciomarine sediments and suspended particulate matter filtered from sea-water were collected in the Weddell Sea during the Norwegian Antarctic Research Expedition (NARE) in 1978–79. Analyses have provided information on the textural and mineralogical composition of shelf sediments, on the nature of biogenic and inorganic suspended particulate matter, and on the total sediment transport to the shelf areas and further into the deeper waters (). The shelf waters contain 0.1 to 1.2 g m–3 of suspended particulate matter, which is close to the range of 0.5 to 1.5 g m–3 reported for suspension concentrations in the oceans, but considerably lower than that found for some other glaciomarine environments such as the Bering Sea {up to 13-15 g m–3 ()) and off Kongsbreen, Spitsbergen {up to 500 g m–3 ()). Suspended particles from the Weddell Sea have maximum sizes of 50 to 70 µm and mean diameters in the range of 10 to 20 µm. In contrast, the bottom sediments on the outer shelf are deficient in the corresponding fractions. This reflects that when floating Antarctic ice supplies material to the Weddell Sea, the coarser fragments (>20-70 µm) are deposited, while the medium silt and finer fractions go into suspension. Considering the suspended-load data and the bottom-current measurements on the shelf break, it is evident that in January 1979 an average of 8.6 × 104tonnes d–1 (or 32 × 106 tonnes a–l) of particulate matter was transported by the current from the central Weddell Sea to the South Atlantic deep water. Morphological (scanning electron microscopy) and chemical analyses show the suspended material to be dominated by silica organisms (diatoms), and also to contain clastic grains of phyllosilicates, feldspar, quartz, zircon, in a few cases Al- and Fe-hydroxides/oxides also; authigenic “Fe-sepiolite” and secondary gypsum. Mineralogical analyses (X-ray diffraction) of the bottom sediments show the fine sand silt fractions to contain mainly clastic materials like illite, smectite-vermiculite, and quartz. Biogenic silica (cristobalite) and carbonate (Mg-calcite) as well as authigenic Fe-silicates (“Fe-sepiolite”) are also present.
Keywords: Sørishavet; glasiologi; sedimenter